Algorithms for the Analytical Solution of the Magnetostatics Inverse Problem for the Signal Source of the Dipole Model - Primin, M.; Nedayvoda, I. (Cybernetics and systems analysis, 2023)
Four variants of the algorithms of the analytical solution of the inverse problem of magnetostatics for the dipolar model of field source are proposed. The solution algorithms are based on the properties of the tensors of the first and second spatial derivatives of the magnetic induction vector. Based on the problem solution method, variants of the spatial configurations of flux transformers of SQUID magnetometric systems and their possible spatial location are proposed. For all the variants of measuring systems, the results of numerical simulation of the solution to the problem of spatial localization of the dipolar source of the magnetic signal are presented.